Does migration make you happy? A longitudinal study of internal migration and subjective well-being - Beata Nowok; Maarten van Ham; Allan M. Findlay; Vernon Gayle (Institute for the Study of Labor (IZA), 2011)
The majority of modelling studies on consequences of internal migration focus almost exclusively on the labour market outcomes and the material well-being of migrants. We investigate whether individuals who migrate within the UK become happier after the move than they were before it and whether the effect is permanent or transient. Using life satisfaction responses from 12 waves of the British Household Panel Survey (BHPS) and employing a fixed-effects model, we derive a temporal pattern of migrants' subjective well-being (SWB) around the time of the migration event. Our findings make an original contribution by revealing for the first time that, on average, migration is preceded by a period when individuals experience a significant decline in happiness. The boost that is received through migration appears to bring people back to their initial level of happiness. As opposed to labour market outcomes of migration, SWB outcomes do not differ significantly between men and women. Perhaps surprisingly, long-distance migrants are at least as happy as short-distance migrants despite the higher social costs that are involved.
urn:nbn:de:101:1-201112136933
Keywords: J61; R23; 330; migration; happiness; subjective well-being; longitudinal data; UK; Binnenwanderung; Zufriedenheit; Großbritannien